Self-esteem, body-esteem, and school performance of selected obese children in Iloilo City. - Martinez, Shelly Anne.; Miralles, Imme Rose. (2003.)
The study sought to examine the levels of self-esteem, body esteem and school performance of selected obese children aged 9-11 years old. Sixteen (16) male and twelve (12)female obese children served as respondents of the study. This study hypothesized that: 1) Obese children have low self esteem; 2) Obese children have low body self esteem; 3) Obese children have low school performance; and 4) There is a gender difference with regard to the three variables oned mentioned., The Piers-Harris Children's self-Concept Scale, modified Body-Esteem scales, and a Teacher's Evaluation for School Performance sheet were utilized for data gathering. Results showed a high level of self-esteem and body-esteem among obese children. The level of scholl performance on the other hand, cannot be determined due to individual differences. Moreover, there was no significant difference on the level of self-esteem and body-esteem in relation to gender since t-values 0.32 and 1.46 were less than t-critical 1.706p<0.05. A significant difference exists for school performance of obese children in relation to gender since t-value 1.82 was greater than t-critical 1.706p>0.05.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Obesity in Children